Quantitative Parameters of Diffusion Spectrum Imaging: HER2 Status Prediction in Patients With Breast Cancer - Mao, Chunping; Jiang, Wei; Huang, Jiayi; Wang, Mengzhu; Yan, Xu; Yang, Zehong; Wang, Dongye; Zhang, Xiang; Shen, Jun (Frontiers in Oncology, 2022)
Objective: To explore the value of quantitative parameters derived from diffusion spectrum imaging (DSI) in preoperatively predicting HER2 status in patients with breast cancer. Methods: In this prospective study, 114 female patients with invasive ductal carcinomas were categorized into HER2-positive group (n = 23) and HER2-negative group (n = 91) depending on the results of pathologic examination. They underwent diffusion-based magnetic resonance imaging (MRI), including diffusion-weighted imaging (DWI) and DSI. Apparent diffusion coefficient (ADC) from DWI, and quantitative parameters from DSI, including diffusion tensor imaging (DTI), diffusion kurtosis imaging (DKI), mean apparent propagator (MAP), and neurite orientation dispersion and density imaging (NODDI), were measured and compared between these two groups. Receiver operating characteristic (ROC) curve analysis was used to assess the discriminative ability of ADC and DSI quantitative parameters. Results: There was no statistically significant difference in ADC values between HER2-positive and HER2-negative groups (P = 0.126). DSI quantitative parameters including axial kurtosis of DKI (DKI_AK), non-Gaussianity (MAP_NG), axial non-Gaussianity (MAP_NGAx), radial non-Gaussianity (MAP_NGRad), return-to-origin probability (MAP_RTOP), and return-to-axis probability of MAP (MAP_RTAP), and intra-cellular volume fraction of NODDI (NODDI_ICVF) were lower in HER2-positive group than that in HER2-negative group (P = 0.00-0.035). DSI quantitative parameters including radial diffusivity (DTI_RD) and mean diffusivity of DTI (DTI_MD), and mean squared diffusion (MAP_MSD) and q-space inverse variance of MAP (MAP_QIV) were higher in HER2-positive group than that in HER2-negative group (P = 0.016-0.049). The ROC analysis showed that the area under curve (AUC) of ADC was 0.632. The AUCs of DSI quantitative parameters ranged from 0.628 to 0.700. Conclusions: DSI quantitative parameters could be used to assist in preoperative prediction of HER2 status in patients with breast cancer.